Pengaruh Kualitas Layanan terhadap Keputusan Nasabah Berinvestasi pada Produk Mudharabah di Bank Muamalat Kutai Timur - Lasmi Laila Lipat Kia; Satriah Satriah; Totok Adhi Prasetyo (PT. Pustaka Andil Lestari, 2025)
This study aims to determine the effect of service quality on customer decisions in investing in mudharabah products at Bank Muamalat Kutai Timur. The background of this study is the importance of the role of service quality in influencing customer interests and decisions, especially in sharia-based investment products such as mudharabah, which prioritize the principles of trust, transparency, and fair cooperation. In the sharia financial system, service quality is one of the key aspects that can determine the loyalty and sustainability of the relationship between the bank and its customers. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who are customers of Bank Muamalat Kutai Timur. Data analysis techniques used include validity, reliability, normality tests, simple linear regression analysis, determination coefficient (R²) tests, and F significance tests. The results of the validity test show that all question items in the questionnaire are declared valid, with a correlation value of > 0.3 and significance < 0.05. The reliability test shows a Cronbach's Alpha value of 0.766 which indicates that this research instrument has good reliability. The results of the regression analysis show that service quality has a positive and significant effect on customer investment decisions. This is indicated by the correlation coefficient (R) of 0.743 and the determination coefficient (R²) of 0.552, which means that 55.2% of customer decision variables can be explained by service quality, while the other 44.8% are influenced by other factors outside this study. The normality test shows that the data is normally distributed, so the basic assumptions of the regression analysis have been met.